Opioid prescribing practices in a pediatric burn tertiary care facility: Is it time to change?. Issue 1 (February 2020) - Khan, Asif; Parikh, Mihir; Minhajuddin, Abu; Williams, Timothy; Abrams, Ruth; Kandil, Enas; Ambardekar, Aditee
Highlights: There is a heavy reliance on opioids for burn analgesia in pediatric patients. Improved use of adjuvant pain therapy might help to minimize opioids use. A high rate of pediatric burn patients received prescription opioids upon discharge. There is minimal use of regional anesthesia for pediatric burn analgesia. Abstract: Opioids are the mainstay therapy in burned adults. Little data in the pediatric burn population exists that elucidates opioid prescribing practices. The primary purpose of this report is to quantify opioid and non-opioid analgesic use in pediatric burn patients admitted to a tertiary referral burn center. A retrospective audit of hospital charts and discharge records for patients <18 years old from March 2016 to March 2017 was performed. Opioid amounts were converted to either oral morphine miligram equivalents (MME) or oral MME per day and subsequently adjusted for age in kilograms (kg). Of the 226 patients, 223 (98.7%) were administered an opioid during admission. The median total opioid amount administered during admission was 0.4 (IQR: 0.3–0.6) mg oral MME per kilogram per day. Anecdotally, doses above 1 mg/kg/day are considered high risk for opioid tolerance. The median total opioid amount prescribed upon discharge was high at 3.9 (IQR: 2.3, 5.6) mg of oral MME per kilogram. Hydrocodone (96.0%) was the most common opioid administered, followed by morphine (88.1%). The most commonly prescribed discharge opioid was hydrocodone (95.4%). Non-opoioid analgesia during admission was used in 112 patients (49.6%). This study provides novel insight into the opioid practices at a tertiary burn center for pediatric patients, with our analysis showcasing high usage of opioids during admission and discharge for burn analgesia. It emphasizes the need to expand beyond opioids for burn analgesia and the importance of promoting non-opioid, multimodal analgesia in the pediatric burn population.